1987
DOI: 10.1002/chin.198725200
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Alkylation of Benzo and Dibenzo Crown Ethers with Different Alcohols.

Abstract: 200 ChemInform Abstract Alkylation of the benzo crown ethers (Ia) with the tertiary alcohols (IIa) and (IIb) gives the tert-alkyl derivatives (Ib), whereas with sec-butanol (IIc) the dialkylated compounds (Ic) and (Id) are obtained. The dibenzo crown ethers (III) give similar results. (IR-, NMR-, MS-data).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Mp 163-164°C. Starting materials were obtained by methods developed in [4][5][6]. The 1 H NMR spectra of initial and final compounds are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Mp 163-164°C. Starting materials were obtained by methods developed in [4][5][6]. The 1 H NMR spectra of initial and final compounds are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Composition of the reaction mixture was controlled by TLC on Merck plates with 1:20:20:1 hexane-chloroform-acetoneethanol as solvent. The starting materials 2a-d were synthesized as we described previously [4]. Compounds 2e,f,g were prepared by the methods of papers [6][7][8] respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is carried out in the presence of HCl, polyphosphoric acid, or polyphosphoric acid ester or by simply fusing the reagents together [1-3]. We chose as the carbonyl compound 4',4"(5")-diacetyl-DB-18-C6 (2a), which we had synthesized earlier [4], since its condensation with the diamine 1 should permit preparation of the required product in a single step. We did not succeed in carrying out the reaction of diamine 1 with the diacetyl derivative in the presence of the condensing agents mentioned above.…”
mentioning
confidence: 99%
“…The structure of these isomers was established earlier [5]. Acylation with lithium and potassium acetates gives a product mostly containing the 4',4"-isomer 1, whereas acylation with sodium acetate leads to a mixture of isomers 1 and 2 with a wider melting range.…”
mentioning
confidence: 87%
“…This product melts at 196-200°C, indicating that it is mainly the 4',4"-isomer 1 (mp of isomer 1 197-199°C, mp of 4',5"-isomer 2 213-215°C [5]). It was found that the length of the process and the composition of the reaction products, according to data from TLC, depend on the cation.…”
mentioning
confidence: 99%